Dialog Menuju Transformasi - Paska, Paskalis Edwin I Nyoman (Perspektif, 2006)
Jesus response to the Canaanite woman "It is not fair to take the children's food and throw it to the dogs" (Matt 15:26) has caused not a few problems of interpretation. How could Jesus call the Canaanite woman a dog, which is a derogatory description of the Gentiles? Who will not be shocked by Jesus' saying? Jesus seems to be out of character. However, did Jesus really intend to despise the woman and the foreigner? It seems that Jesus' saying should be understood as a usage of rhetoric language. That is to say, Jesus was not expressing His understanding but He was quoting Israel's conception of woman and Gentiles in order to refuse and to correct it. In other words, He said this derogatory ironically to remind the Israelites how bad and incorrect their conception of God's salvation was. On the other hand, as a Jew, Jesus was probably influenced by Jewish conception of woman and Gentiles. Matt 15:24, for instance, expresses how Jesus sees His mission as exclusively devoted to Israel. The fact that by the end of the story Jesus conceives the salvation as open to Gentiles shows that Jesus was transformed as well. Jesus' encounter and dialog with the Canaanite Woman transformed not only the Canaanite woman but also Jesus' perception of the Canaanite woman and Jesus' understanding of His own mission. At the beginning, He perceived the woman as a worthless person. By the end, He recognized her as someone with great faith and worthy for salvation. Thus, an encounter and a dialog with a person from different culture bring transformation of the both partners of dialog.